Interpretacja i profilowanie klas w analizie danych symbolicznych - Wilk, Justyna (Cluster Interpretation in Symbolic Data Analysis, 2007)
There was presented the way of cluster interpretation in symbolic data analysis in the paper. Firstly the idea and the types of symbolic variables were defined. Then two ways of classification procedure for symbolic objects were suggested. After that the ways of cluster interpretation of symbolic objects were characterized according to classification procedure, with numerical examples.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 149-159